Identification of CXCL10 and CXCL11 as the candidate genes involving the development of colitis-associated colorectal cancer - Lu, Can; Zhang, Xiaopeng; Luo, Yang; Huang, Jingang; Yu, Minhao (Frontiers in Genetics, 2022)
Background Ulcerative colitis (UC) is a well-known risk factor for developing colitis-associated colorectal cancer (CAC). However, the molecular mechanism of the pathogenesis of CAC remains unclear. This study aimed to explore candidate genes involving the tumorigenesis of CAC. Methods GSE75214 and the Cancer Genome Atlas Program (TCGA) dataset were used to analyze the differential expression genes (DEGs) in UC and colorectal cancer (CRC), respectively. The survival-hub genes were identified from these DEGs via sequentially constructing a protein-protein interaction network, selecting hub genes, and conducting survival analysis. Regulatory signatures were also predicted on these genes through the online database. Apcmin/+ and UC mice models were used to validate the expression of the above-predicted molecules. Gene set enrichment analysis and CIBERSORT were performed to explore the enriched molecular pathways and associated tissue-infiltrating immune cells of genes. Results 376 common DEGs were identified from GSE75214 and TCGA datasets. Through survival-hub genes selection and in vivo experiments, we confirmed that CXCL10 and CXCL11 were significantly up-regulated in UC and CRC. We also proved that miR-34a-5p and miR-203a-5p were potential regulators of CXCL10 and CXCL11. Meanwhile, CXCL10 and CXCL11 may activate the JAK-STAT signaling pathway via the interaction with cytokine receptors in UC. Furthermore, CXCL10 and CXCL11 were positively associated with the tissue infiltration of pro-inflammatory M1 macrophages in UC and CRC. Conclusion CXCL10 and CXCL11 may act as the candidate genes involving the tumorigenesis of CAC and potential therapeutic targets to prevent the development of CAC from UC.